2017
DOI: 10.1148/radiol.2016152362
|View full text |Cite
|
Sign up to set email alerts
|

Thin-Section CT Features of Idiopathic Pulmonary Fibrosis Correlated with Micro-CT and Histologic Analysis

Abstract: Purpose To elucidate the underlying lung changes responsible for the computed tomographic (CT) features of idiopathic pulmonary fibrosis (IPF) and to gain insight into the way IPF proceeds through the lungs and progresses over time. Materials and Methods Micro-CT studies of tissue cores obtained from explant lungs were examined and were correlated 1:1 with a CT study obtained immediately before transplantation. Samples for histologic analysis were obtained from selected cores. Results In areas with no or minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 33 publications
1
56
0
1
Order By: Relevance
“…Recently, Mai et al 29 reported that even in areas with no or minimal abnormalities on CT images, there were islands of increased attenuation located in or near the interlobular septa on micro-CT scans. These areas corresponded to fibroblastic foci (ie, active, very recently formed fibrotic areas) at histologic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Mai et al 29 reported that even in areas with no or minimal abnormalities on CT images, there were islands of increased attenuation located in or near the interlobular septa on micro-CT scans. These areas corresponded to fibroblastic foci (ie, active, very recently formed fibrotic areas) at histologic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The main limitation of the present study was the lack of pathologic examination of lungs, which prevents histologic proof of the nature of lesions identified by CT, and allows the possibility that there were age‐related lung changes that were undetected by CT. All CT studies reviewed in this study were obtained using settings suitable for clinical assessment of the lung of dogs, but more detailed assessment is possible using thinner (1 mm) CT slices or micro‐CT with histologic examination of precisely orientated lung sections. Further studies are indicated to better examine imaging–pathologic correlations in the aging canine lung.…”
Section: Discussionmentioning
confidence: 99%
“…Coxson and coworkers performed a quantitative morphological study in IPF lungs and observed that the main consequence of IPF on lung structure is a dramatic decline in surface area of the alveolar epithelium (12) so that it has been discussed very comprehensively that alveolar collapse and collapse induration are extremely important pathological events in fibrosing lung diseases (35,46,67). Also, micro-CT studies from human IPF suggest that alveolar collapse takes place at a very early stage of the disease in the absence of severe fibrotic remodeling so that it obviously predates collagen deposition in IPF (41). Structure-function relationships in the bleomycin model of lung injury and fibrosis showed that the number of open alveoli per lung was highly correlated with lung mechanical impairment (39).…”
mentioning
confidence: 99%